EFFECTIVENESS OF TEACHER-MADE TESTS IN GOROMONZI DISTRICT PRIMARY SCHOOLS - MUZENDA, DOCTOR DENIAS (IJRDO- Journal of Educational Research, 2017)
This study sought to establish the effectiveness of teacher-made tests on the performance ofpupils in Goromonzi District in Mashonaland East Province in Zimbabwe. The study used thepositivistic paradigm and adopted the descriptive survey design. The population comprised of allprimary schools in Goromonzi district. The sample consisted of 240 teachers from 30 schoolsrandomly selected. Each school provided 8 teachers for the study. Of the sample respondents130 were female and 110 male. All the information was collected through a questionnaire whichhad both close-ended and open-ended questions. Descriptive statistical analysis was used tointerpret data. The results of the study indicate that teacher-made tests are given to pupils in theschools and there was overwhelming acceptance by the respondents that these tests helped toimprove the academic performance of pupils. It was also found that most teachers did not haveknowledge about the standard procedures of constructing, marking, scoring and grading of tests.The study recommends that there was need for schools to conduct staff developmentprogrammes to equip teachers with skills to construct teacher-made tests